Pemekaran pemerintahan nagari :: Studi tentang pemekaran Pemerintahan Nagari Lunang Kabupaten Pesisir Selatan - ALAMSYAH, Mar ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The Birth of Law No. 22 of 1999 concerning about Regional Government - who later revised by Law No. 32 of 2004 - was swept up in the era of reform, which the law focused on the decentralization that provides flexibility for regions to manage and organize his administration or more commonly known as the Regional Autonomy includes the lowest setting on the government with respect to local forces in the region. In West Sumatra, exploited the opportunity by passing the Regional Regulation (Perda) West Sumatra Province No. 9 Year 2000 about Main Provisions Nagari government which became a guide for the 8 (eight) districts in West Sumatra to develop laws governing the village government in the region. With the enactment of this law, then the system of government gradually removed and replaced the village with village government system in accordance with the culture of Minangkabau culture. But, back to the government village system today is not a pure return to the village as the local self-government but try to combine them with - even more similary- local state government, because it was in at a village now not only look to her with authentic cultures and Minangkabau culture but also as the vanguard of the lowest government services. The reason for this later in a decision about the possible existence of village government expansion with no customary village blossom. The study, entitled "Expansion of Government Nagari: Study About Redistricting Lunang Nagari Government of Pesisir Selatan regency" with the purpose of research to understand and explain the factors which technocratic and political reason for the expansion Lunang Nagari. Type of research is descriptive research with a qualitative approach, while the data collection techniques with depth Interviews, Observation (observe) and Documentation. The results showed that the division of real Lunang Nagari Government through a long process that starts from the year 2004 the then newly realized in 2009 with the adoption of the Pesisir Selatan Regency Regulation No. 50-53 to divide Lunang Nagari in 4 (four) village administration. The factor or reason to split Lunang Nagari government is that factor of technocratic reason for the lack of services due to the vast area village, village governance effectiveness reasons and economic reasons. However, these technocratic factors only become "packaging" of the hidden political factors. This is what political factors are more dominant in the division of the Government as Lunang Nagari wants to distribution of power, want to separate the government based on tribal identity (between the Minangkabau and Javanese) and to obtain large DAUPN of the regency. Besides the political reasons for this can be seen from the large villages will create as a first step to form a new district which ultimately aim to form a regency with a Renah Indojati regency.